The Victorian world : a historical exploration of literature - DeLong, Anne (Historical explorations of literature., 2019)
This book examines the historical, political, social, and cultural contexts of several important Victorian literary works: Jane Eyre, by Charlotte Bronte; Wuthering Heights, by Emily Bronte; A Tale of Two Cities, by Charles Dickens; and several poems by Elizabeth Barrett Browning, including "The Cry of the Children," "The Runaway Slave at Pilgrim's Point," "A Curse for a Nation," and Aurora Leigh.